2016
DOI: 10.1007/s00246-016-1532-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Plasma Levels of Cardiac Myosin Binding Protein-C as a Novel Biomarker in Heart Failure

Abstract: Heart failure (HF) has high morbidity and mortality in children. This study aimed to investigate the value of cardiac myosin binding protein-C (cMyBP-C) as a diagnostic and prognostic biomarker in children with heart failure. This study was a prospective case-control study that involved 50 children with acute HF and 25 healthy children of matched age and sex as a control group. cMyBP-C plasma levels were measured in patients with HF at the time of admission and 1 month after treatment. Echocardiographic assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…The exact release mechanism of cMyBP-C in heart failure is still unknown. Moreover, cMyBP-C has a 90% sensitivity and 93% specificity as a biomarker of prognosis in heart failure patient at cutoff value of 152 ng/ml [48]. The same study showed that failure to decrease the level of serum cMyBP-C leads to poor prognosis.…”
Section: Cmybp-c As Biomarker For Dcm and Heart Failurementioning
confidence: 84%
See 1 more Smart Citation
“…The exact release mechanism of cMyBP-C in heart failure is still unknown. Moreover, cMyBP-C has a 90% sensitivity and 93% specificity as a biomarker of prognosis in heart failure patient at cutoff value of 152 ng/ml [48]. The same study showed that failure to decrease the level of serum cMyBP-C leads to poor prognosis.…”
Section: Cmybp-c As Biomarker For Dcm and Heart Failurementioning
confidence: 84%
“…Dilated Cardiomyopathy is a common cause of heart failure, affecting the heart musculature and vasculature and involves one or several underlying pathophysiological mechanisms [47]. Myocyte injury can lead to DCM and causes release of related biomarkers including that of cMyBP-C. At cutoff value of 45 ng/ml, serum cMyBP-C turns out to have 100% sensitivity and 96% specificity as diagnostic biomarker for heart failure [48]. The exact release mechanism of cMyBP-C in heart failure is still unknown.…”
Section: Cmybp-c As Biomarker For Dcm and Heart Failurementioning
confidence: 99%
“…With the use of a cut‐off concentration of 45 ng/mL, the sensitivity reached 100% and its specificity for diagnosing AHF was 96%, while at the cut‐off concentration of 152 ng/mL, its sensitivity and specificity for predicting adverse outcomes were as high as 90% and 93%, respectively. The AUC was 0.999 (95% CI 0.997–1.002) for the diagnosis and 0.915 (95% CI 0.796–1.034) for the prognosis of AHF 30 . However, comparisons between the results of the two studies should be assessed with caution, mainly since the aetiology of AHF in children with a mean age < 2 years in this study substantially differed when compared to the elderly adult AHF population as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the etiology, neurohormonal activation plays an important role in the pathophysiology of the development and progression of HF [ 2 ]. The renin angiotensin aldosterone system (RAAS) as well as vasopressin (VP) and the sympathetic nervous system are activated in cases of HF leading to salt and water retention, vasoconstriction, and increased heart rate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%